AKHLAKI SUFISM ANALYSIS WITHIN KH. M. BAHRUDDIN - Fanani, Sukron (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan)
Sufism or salik perpetrators were mostly scholars or clerics institutes play an important role for the life of him, his followers and the surrounding communities. Because of his relationship with a teacher of Islam is not just the relationship between a leader and his people, but also the relationship between teacher and pupil always said sami'na waatha'na,which means that we hear and we obey. Salik either of scholars or clerics who have students / schools or otherwise, is very influential in the social order around, especially on scholars / clerics that has followers that one example of the figure of the religious scholars are KH. M. Bahruddin.